Pseudo-Skolem sequences and graph Skolem labelling - Pike, David A.; Sanaei, Asiyeh; Shalaby, Nabil (MATHEMATICA SCANDINAVICA, 2017)
Pseudo-Skolem sequences, which are similar to Skolem-type sequences in their structure and applications, are introduced. Constructions of such sequences, either directly or via the use of known Skolem-type sequences, are presented. The applicability of these sequences to Skolem labelled graphs, in particular classes of rail-siding graphs and caterpillars, are also discussed.